Religious Consistency and Commitment to Local Tradition Within the Bawakareng Community in Indonesia’s South Sulawesi - Mustaqim Pabbajah (Graduate Program of Pontianak Institute of Islamic Studies, 2020)
Islam and local traditions have been struggling dynamically as seen in the reality of the social and religious life in the Indonesian context. This study aims to reaffirm the relationship between religion and local traditions by observing the consistency of South Sulawesi’s Bawakaraeng community in practicing both Islam and local traditions. This work is based on data collected through observation, interviews, and literature studies with a qualitative descriptive analysis approach. The results of this study show three findings. First, the Bawakaraeng community, represented by some people of Buginese and Macassarese ethnic groups, still believes that a local mountain is the center of a ritual to get closer to the creator. Second, the community has not only a strong consistency in the practice of Islamic teachings, but also a high commitment to maintaining local traditions, as practiced by Bawakaraeng community members. Third, religious consistency and a commitment to local traditions are practiced simultaneously through worshiping rituals such as prayers, remembrances, alms, and the pilgrimage activities (qurban-scarification) and tawaf). Thus, the Islamic spirits are being practiced consistently and continuously within the community’s local context. This study suggests further undiscovered research on local communities using a contextual approach.